Development of a broad-spectrum Salmonella phage cocktail containing Viunalike and Jerseylike viruses isolated from Thailand. (December 2020) - Phothaworn, Preeda; Supokaivanich, Rattaya; Lim, Jiali; Klumpp, Jochen; Imam, Mohammed; Kutter, Elizabeth; Galyov, Edouard E.; Dunne, Matthew; Korbsrisate, Sunee
Abstract: Salmonella is one of the most common agents of foodborne disease worldwide. As natural alternatives to traditional antimicrobial agents, bacteriophages (phages) are emerging as highly effective biocontrol agents against Salmonella and other foodborne bacteria. Due to the high diversity within the Salmonella genus and emergence of drug resistant strains, improved efforts are necessary to find broad range and strictly lytic Salmonella phages for use in food biocontrol. Here, we describe the isolation and characterization of two Salmonella phages: ST-W77 isolated on S . Typhimurium and SE-W109 isolated on S . Enteritidis with extraordinary Salmonella specificity. Whole genome sequencing identified ST-W77 as a Myovirus within the Viunalikevirus genus and SE-W109 as a Siphovirus within the Jerseylikevirus genus. Infectivity studies using a panel of S . Typhimurium cell wall mutants revealed both phages require the lipopolysaccharide O-antigen, with SE-W109 also recognizing the flagella, during infection of Salmonella . A combination of both phages was capable of prolonged (one-week) antibacterial activity when added to milk or chicken meat contaminated with Salmonella . Due to their broad host ranges, strictly lytic lifestyles and lack of lysogeny-related genes or virulence genes in their genomes, ST-W77 and SE-W109 are ideal phages for further development as Salmonella biocontrol agents for food production. Highlights: Isolation of broad range phages capable of killing antibiotic-resistant Salmonella . Siphovirus SE-W109 requires O-antigen and flagella for complete infectivity. Combination of ST-W77 and SE-W109 prolong antibacterial activity in food. Both phages retain infectivity in 3% NaCl and at 40 °C for 1 h.